Software for Computing the Tetrachoric Correlation Coefficient - Ledesma, Ruben Daniel (2011)
Tetrachoric correlation is a special case of analysis of the statistical covariation between two variables measured on a dichotomous scale, but assuming an underlying bivariate normal distribution. Computation of tetrachoric correlation is not straightforward and is usually not available in standard statistical packages. This paper introduces ViSta-Tetrachor, a plug-in for the statistical package ViSta that computes the tetrachoric correlation using an approximation that has shown to be both accurate and simpler to compute than the original algorithm. Additionally, ViSta-Tetrachor provides point and interval estimates for this statistic. Such feature is very uncommonly found in standard statistical packages. ViSta-Tetrachor also allows for computing tetrachoric correlation matrices that can subsequently be analyzed with the ViSta’s Factor Analysis module. A brief description of the software is presented with several worked examples.